Bilingual service at hostels in the city of São Paulo (Research, Society and Development, 2020)
The increase in foreign tourism that occurs in the city of São Paulo reflected in the diversification of the innumerable means of accommodation. The hostel presents itself as an economical tourist option and serves mainly a young portion of foreign tourists. Thus, in order to better serve guests visiting the localities, effective and satisfactory communication must be established. The study proposes bilingual service in hostels. The research method is characterized as a qualitative study. The approaches used were: exploratory, in order to gather information in official documents, and descriptive, in order to draw a current panorama of the hostels in the city. The work started with the search for better hostels, based on consultations on the four most popular accommodation sites in the country. The survey was carried out in August 2019. Within that period, six establishments participated in the study. The results show that the hostels consider themselves prepared to serve this audience. Finally, it is observed that a good service and bilingual visual communication can provide accessibility in the city and lead to a greater number of international tourists who seek a harmonious environment and interpersonal experiences, which promotes cultural exchanges, as well as incentives for the city to become make it increasingly accessible to all peoples.